2014
DOI: 10.1371/journal.pone.0114471
|View full text |Cite
|
Sign up to set email alerts
|

A Laboratory Prognostic Index Model for Patients with Advanced Non-Small Cell Lung Cancer

Abstract: PurposeWe aimed to establish a laboratory prognostic index (LPI) in advanced non-small cell lung cancer (NSCLC) patients based on hematologic and biochemical parameters and to analyze the predictive value of LPI on NSCLC survival.Patients and MethodsThe study retrospectively reviewed 462 patients with advanced NSCLC diagnosed between 2000 and 2010 in a single institution. We developed an LPI that included serum levels of white blood cells (WBC), lactate dehydrogenase (LDH), albumin, calcium, and alkaline phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
45
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 30 publications
6
45
2
1
Order By: Relevance
“…Consitent with other reports (22), in the present study, low levels of 5-hmC were more common in patients with lymph node metastases, high histological types and large tumor sizes, which are recognized prognostic factors for lung cancer (23). The proportion of low 5-hmC level in NSCLC patients with lymph node metastases was markedly higher than those patients without lymph node metastases, as well as the histological types and tumor sizes.…”
Section: -Hmc Level ---------------------------------------------------supporting
confidence: 83%
“…Consitent with other reports (22), in the present study, low levels of 5-hmC were more common in patients with lymph node metastases, high histological types and large tumor sizes, which are recognized prognostic factors for lung cancer (23). The proportion of low 5-hmC level in NSCLC patients with lymph node metastases was markedly higher than those patients without lymph node metastases, as well as the histological types and tumor sizes.…”
Section: -Hmc Level ---------------------------------------------------supporting
confidence: 83%
“…LDH can be released during tissue damage and is involved in tumor initiation and metabolism. Numerous studies have shown that LDH activity is an indicator of metastatic risk and could be an important prognostic factor in a variety of cancers (Weide et al 2013;Cetin et al 2014;Philipp et al 2014;Ulas et al 2014;Liu et al 2015). The use of LDH as a prognostic factor in SCLC has also been demonstrated over recent decades (Tas et al 2001;Bremnes et al 2003;Hermes et al 2010).…”
Section: Discussionmentioning
confidence: 98%
“…The authors suggested that albumin and LDH levels might be used in the risk scoring in further studies. Further studies demonstrated that serum albumin level was a critical prognostic factor in the lung cancer (Forrest et al, 2003;Kasymjanova et al, 2010;Leung et al, 2012;Trape et al, 2012;Gagnon et al, 2013;Jafri et al, 2013;Ulas et al, 2014). In these studies, prognostic risk models were created using a number of clinical and laboratory variables and low serum albumin level was found to be one of the poor prognostic factors in the majority of the scoring systems.…”
Section: 5971 Serum Albumin As a Prognostic Factor With Stage Iiib Nmentioning
confidence: 99%
“…With the introduction of recent findings, the Glasgow Prognostic Score (GPS) and the Advanced Lung Cancer Inflammation Index (ALI) on the basis of serum albumin and CRP level have been developed. In addition, further scoring systems such as modified-GPS, Prognostic Index (PI), Adverse Prognostic Factors (APF), and the Montreal Prognostic Score (MPS) based on the performance status, CRP, tumor markers such as carbohydrate antigen (CA)-125, and inflammatory markers such as leukocycte and neutrophil/lymphocyte ratio have been developed (Forrest et al, 2003;Kasymjanova et al, 2010;Leung et al, 2012;Trape et al, 2012;Gagnon et al, 2013;Jafri et al, 2013;Ulas et al, 2014). In the majority of these studies, many patients had a metastatic disease (Forrest et al, 2003;Kasymjanova et al, 2010;Leung et al, 2012;Trape et al, 2012;Gagnon et al, 2013;Jafri et al, 2013;Ulas et al, 2014).…”
Section: 5971 Serum Albumin As a Prognostic Factor With Stage Iiib Nmentioning
confidence: 99%
See 1 more Smart Citation